The Influence of College Physical Education Teaching on Students’ Mental Health and Skill Improvement under the embodied cognition Theory - Chunying Ma (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The research aimed to check the influence of college physical education teaching on students' mental health and skill improvement under the embodied cognition theory. The study conducted using a mixed-methods approach, incorporating both quantitative and qualitative data collection methods data collection methods to comprehensively understand the effects of sports dance teaching on students' physical and mental well-being, aesthetic awareness, and cultural cultivation. The research involved 130 sophomore students from a provincial university who voluntarily participated in the sports dance teaching program. Quantitative data was collected using the SCL-90 self-assessment scale to evaluate the students' mental health and psychological well-being. Questionnaires were distributed twice, at the beginning and end of the semester, to obtain pre-and post-teaching data. The analysis of 120 collected questionnaires showed a significant improvement in the students' mental health levels after the sports dance teaching. The study found that sports dance effectively exercises the cardiovascular system, improves cardiovascular function and endurance, and contributes to body shaping and weight loss. Moreover, participating in sports dance positively impacted students' mental health, reducing factors like depression and hostility, and enhancing interpersonal relationships. The embodied cognition teaching mode played a vital role in regulating and promoting mental health, establishing healthy personalities, and improving aesthetic awareness and cultural cultivation. The sports dance program also enhanced students' music accomplishment, rhythm abilities, learning capacity, and cooperation skills. It fostered a sense of collaboration, friendship, trust, and unity among the students, helping them develop a noble character and a positive outlook on life and the world. Limitations and future directions were also addressed at the end of the study.